Synthesis and Characterization of Hierarchical Porous α-FeOOH for the Adsorption and Photodegradation of Rhodamine B. (18th February 2014) - Cao, Jianliang; Li, Gaojie; Wang, Yan; Sun, Guang; Bala, Hari; Wang, Xiaodong; Zhang, Zhanying
Abstract : Hierarchical porous α -FeOOH nanoparticles were controlled and prepared via a facile polystyrene (PS) microspheres-templated method. The α -Fe2 O3 was obtained by the calcination of the as-prepared α -FeOOH. The resulting nanoparticles were characterized by X-ray diffraction analysis (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and N2 -sorption techniques. The adsorption and photodegradation of Rhodamine B performance were evaluated under UV light at room temperature. The results indicated that the photocatalytic activity of the α -FeOOH nanoparticles is superior to α -Fe2 O3 -200 and α -Fe2 O3 -300 due to the hierarchically multiporous structure and high surface area. This convenient and low-cost process provides a rational synthesis alternative for the preparation of multiporous materials and the as-synthesis products have great foreground applications in many aspects.